1995
DOI: 10.1037/0278-6133.14.3.217
|View full text |Cite
|
Sign up to set email alerts
|

Risk-perception: Differences between adolescents and adults.

Abstract: This study investigated age changes in risk perception and unrealistic optimism. Teenagers (« = 376) and parents (n = 160) evaluated the risk of experimental, occasional, and regular involvement in 14 health-related activities (e.g., getting drunk). Respondents also evaluated their comparative chances of encountering the leading causes of morbidity and mortality. Compared with adults, teenagers minimized the perceived risk of experimental and occasional involvement in health-threatening activities. Notably, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
185
3
17

Year Published

2000
2000
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(216 citation statements)
references
References 19 publications
11
185
3
17
Order By: Relevance
“…Therefore, risk perception is considered a precursor of actual driving behaviour. Many researchers have indicated that risk perception is negatively related to risk behaviour in general (Cohn, Macfarlane, Yanez, & Imai, 1995). That is, a higher level of perceived risk for a particular behaviour is associated a lower chance that an individual would take part in that behaviour.…”
Section: The Influence Of Risk Perceptionsmentioning
confidence: 99%
“…Therefore, risk perception is considered a precursor of actual driving behaviour. Many researchers have indicated that risk perception is negatively related to risk behaviour in general (Cohn, Macfarlane, Yanez, & Imai, 1995). That is, a higher level of perceived risk for a particular behaviour is associated a lower chance that an individual would take part in that behaviour.…”
Section: The Influence Of Risk Perceptionsmentioning
confidence: 99%
“…Para ambos os grupos etários, e para todos os eventos com exceção da gripe, as diferenças entre os julgamentos face ao próprio e face ao alvo foram significativamente superiores a zero. Estes dados vêm reforçar as escassas evidências que mais recentemente se encontram na literatura e que, também elas, mostram a prevalência deste fenômeno entre os mais jovens (Arnett, 2000;Chapin et al, 2005;Cohn et al, 1995;Gladis et al, 1992;Quadrel et al, 1993;Whalen et al, 1994).…”
Section: Discussionunclassified
“…De fato, evidências empíricas recentes vêm suportar a relação positiva entre a presença de crenças de fábula pessoal e percepções de invulnerabilidade comparativa na adolescência, especificamente em relação a ser vítima de violência (Chapin, de las Alas, & Coleman, 2005). Todavia, apesar desta teoria ser uma das mais citadas, apontando para um pico na percepção de invulnerabilidade ao risco na adolescência, é uma hipótese fundamentalmente assente em evidências clínicas e que, atualmente, apresenta escassas evidências empíricas que a suportem (Cohn, Macfarlane, Yanez, & Imai, 1995;Millstein, 1993;Quadrel et al, 1993).…”
unclassified
See 2 more Smart Citations